Relationship of Functional Reach Test scores and falls in Special Olympics athletes. Issue 6 (14th February 2019) - Thomas, J.; O'Neal, S.
Abstract: Background: The Functional Reach Test is used to assess balance of Special Olympic athletes as part of the FUNfitness screens held at Special Olympics games. However, it is unknown if the Functional Reach Test is an accurate assessment of balance in this population. The objective of this study was to explore the relationship between Functional Reach Test scores and falls in Special Olympic athletes. Methods: Data were collected as a part of the FUNfitness screens during Arizona Special Olympics games. The Functional Reach Test scores of 272 Special Olympic athletes were recorded. Athletes were asked to report the number of falls they experienced in the last 12 months. Results: A two‐tailed Kendall tau test revealed little to no relationship between number of falls and Functional Reach Test scores of either the left upper extremity ( n = 263, τ = −0.063, P = 0.202) or the right upper extremity ( n = 263, τ = −0.107, P = 0.030). Sensitivity of the Functional Reach Test to identify fallers was 28.8%, and specificity was 83.5%. Conclusions: Scores of the Functional Reach Test did not correlate with actual falls. The relatively high specificity indicates the assessment is good at identifying non‐fallers, while the low sensitivity results in a high number of fallers not being recognised as such. Therefore, the cut‐off scores used for the Functional Reach Test in FUNfitness screenings may need to be altered to more accurately identify balance deficits in this population. FUNfitness screens need to be quick, efficient and accurate. As such, selection of the most appropriate assessment tools is essential. Consideration should be given on how to make the Functional Reach Test the most beneficial as a FUNfitness screen.